Experience of Kenyan researchers and policy-makers with knowledge translation during COVID-19: a qualitative interview study. Issue 6 (1st June 2022) - Guleid, Fatuma Hassan; Njeru, Alex; Kiptim, Joy; Kamuya, Dorcas Mwikali; Okiro, Emelda; Tsofa, Benjamin; English, Mike; Molyneux, Sassy; Kariuki, David; Barasa, Edwine
Abstract : Objectives: Researchers at the KEMRI-Wellcome Trust Research Programme (KWTRP) carried out knowledge translation (KT) activities to support policy-makers as the Kenyan Government responded to the COVID-19 pandemic. We assessed the usefulness of these activities to identify the facilitators and barriers to KT and suggest actions that facilitate KT in similar settings. Design: The study adopted a qualitative interview study design. Setting and participants: Researchers at KWTRP in Kenya who were involved in KT activities during the COVID-19 pandemic (n=6) were selected to participate in key informant interviews to describe their experience. In addition, the policy-makers with whom these researchers engaged were invited to participate (n=11). Data were collected from March 2021 to August 2021. Analysis: A thematic analysis approach was adopted using a predetermined framework to develop a coding structure consisting of the core thematic areas. Any other theme that emerged in the coding process was included. Results: Both groups reported that the KT activities increased evidence availability and accessibility, enhanced policy-makers' motivation to use evidence, improved capacity to use research evidence and strengthened relationships. Policy-makers shared that a key facilitator of this was the knowledge products shared and the regular interaction with researchers. Both groups mentioned that a key barrier was the timeliness of generating evidence, which was exacerbated by the pandemic. They felt it was important to institutionalise KT to improve readiness to respond to public health emergencies. Conclusion: This study provides a real-world example of the use of KT during a public health crisis. It further highlights the need to institutionalise KT in research and policy institutions in African countries to respond readily to public health emergencies.